OP0058 Efficacy of infliximab in severe refractory ankylosing spondylitis (as). results of an open-label study. (1st June 2001) - Breban, MA; Vignon, E; Claudepierre, P; Saraux, A; Wendling, D; Lespesailles, E; Euller-Ziegler, L; Sibilia, J; Perdriger, A; Alexandre, C; Dougados, M
Abstract : Background: Early reports have emphasised the efficacy of the anti-TNF-alpha monoclonal antibody, infliximab, to treat spondylarthropathy patients. Further studies are required to evaluate the extent of such efficacy in large subgroups of well-defined patients. Objectives: To examine the effect of infliximab, in severe AS with predominant axial symptoms. Methods: Patients suffering of severe AS, with evidence of systemic inflammation (modified New-York criteria; BASDAI > = 30/100; CRP > = 15 mg/l)), and without present peripheral arthritis or extraskelettal manifestation were included. Previous DMARD's had to be discontinued for > = 3 months. Intake of NSAID had to be stable. Eligible patients received 3 infusions of infliximab (5 mg/kg, weeks 0, 2 and 6). Clinical and biological monitoring was planned for 6 months. Results: We enrolled 48 parents (36 M/12 F; mean age = 36 ± 9 yr); 41/46 (89%) were HLA-B27+; 43 (90%) completed the treatment, as scheduled, whereas 5 received only 2 infusions. Interim result (wk 8) is shown, and compared to baseline in the table. Altogether, 44 patients (92%) were responders, as defined by a reduction of global pain on VAS of at least 20%, as compared to baseline level. Conclusion: Our data confirm the remarkable efficacy of infliximab in AS. It indicate that most, patients suffering of inflammatory active AS promptly and dramatically respond to this treatment.